Healthy Living: Are You at Risk for Dehydration? - Jennifer Hillan (EDIS)
FCS8847, a 1-page fact sheet by Jennifer Hillan, provides a short quiz that users can take to find out if they are at risk for dehydration and subsequent problems. Published by the UF Department of Family, Youth and Community Sciences, September 2007.